The Warp and weft of heritagizing likhang-bayan textiles - Icasiano, Carmita Eliza J. (Saliksik kultura: the NCCA Research Journal, 2021)
Philippine traditional craft objects I refer to as “likhang-bayan” are textiles, woodcarving, paper craft, metalcraft, basketry, and pottery that lean on traditions of making, and produced using techniques surviving from a town’s cultural past. These heritage objects, while tangible, are inextricably connected to an intangible heritage which encompasses artisanal making. As heritage goods, likhang-bayan are subjected to processes of heritagization, folklorization, and festivalization, mediated not only by the state and cultural agencies but also by retail stores and social enterprises. This paper focuses on and examines the ways in which likhang-bayan textiles have been subjected to these processes in market fairs, exhibits, retail and souvenir shops, and in social media that propose to reform the public’s attitudes and understandings about what constitutes heritage and its relationship to contemporary everyday life.